Coordinated Scheduling of Automated Loading Platforms in Commercial Logistics - Xiaoqian Nie; Lu Qin; Zixuan Peng; Chuanhan Zhou (Journal of Advanced Transportation)
Automated warehousing and distribution has been an innovation approach to reduce costs and increase efficiency in logistics industry. Taking the intelligent demonstration warehouse in a commercial logistics park in Shandong, China as the background, this paper constructs a platform resource scheduling model under the Automatic Guided Vehicle (AGV) sharing mode to solve the problems of platform allocation and equipment scheduling, and solves it using the simulated annealing algorithm. This paper designs First-Come, First-Served (FCFS) rule, platform resource scheduling rules when AGVs are used separately, and platform resource scheduling rules when AGVs are shared, outputting platform operation scheduling schemes. Meanwhile, different numbers of AGVs are scheduled under the AGV sharing mode to validate the model and algorithm. The results show that the platform resource scheduling model proposed in this paper improves the platform utilization rate by 4.4% compared to the traditional FCFS rule, and the latest departure event is advanced by 95 min. The AGV sharing mode can complete vehicle loading tasks in a shorter time and with faster operational efficiency.